Controllable splitting dynamics of a doubly quantized vortex in a ring-shaped condensate. (11th March 2020) - Xiong, Bo; Yang, Tao; Lin, Yu-Ju; Wang, Daw-Wei
Abstract: We prepared a ring-shaped Bose–Einstein condensate with quantized circulation by imprinting a linear azimuthal phase. A doubly quantized vortex (DQV) can be generated and exist stably in the middle of the condensate cloud after the system is released into a rotationally symmetric harmonic trap. For an asymmetric trap with a small degree of anisotropy the generated DQV initially splits into two singly quantized vortices and revives again but eventually evolves into two unit vortices due to the dynamic instability. For the degree of anisotropy above a critical value, the DQV is extremely unstable and decays rapidly into two singlet vortices. The geometry-dependent lifetime of the DQV and vortex-induced excitations are also discussed intensively.